KECEMASAN PERAWAT MASA PANDEMI COVID 19: TINJAUAN LITERATURE - Juwi Athia Rahmini; Widyawati - (Jurnal Keperawatan Priority, 2022)
The anxiety experienced by nurses during the COVID-19 pandemic is a feeling that cannot be avoided and affects the performance of nurses in providing nursing care.  The purpose of article aims to describe nurses' anxiety during the COVID-19 pandemic. The method used is Narrative literature review by searching articles from Google Scholar dan DOAJ  database with keyword nurse anxiety in COVID-19. The result of those articles are nurses experienced anxiety in providing nursing care during the COVID-19 pandemic. This anxiety is associated with age, female gender, experience, inadequate availability of personal protective equipment, lack of training on preparedness to face the COVID-19 pandemic outbreak. Nurses experience anxiety in carrying out nursing care during the COVID-19 pandemic. The government within hospital policies can anticipate intervening psychologically for nurses during a pandemic, such as providing consulting services, the availability of adequate personal protective equipment, and training for preparedness to face the COVID-19 pandemic effectively.